The Influence of Work Flexibility and Internal Social Media on the Work Effectiveness of Generation Z Employees: The Mediating Role of Hybrid Work Engagement - Ferdiyanto, Yusriel Arief; Frimayasa, Agtovia (Jurnal Multidisiplin Sahombu, 2025)
This study investigates the influence of work flexibility, internal social media, and hybrid work engagement on employee effectiveness in modern organizational contexts. Using a quantitative approach with structural equation modeling, the research explores both direct and indirect relationships among the variables. The results indicate that internal social media plays a pivotal role in enhancing work effectiveness by fostering communication, collaboration, and knowledge sharing within organizations. Hybrid work engagement also demonstrates a strong influence, as engaged employees in flexible environments are more committed, adaptive, and productive. Although work flexibility does not directly improve effectiveness, it contributes indirectly by encouraging greater use of internal social media, which subsequently enhances performance. These findings underscore the importance of integrating digital communication tools and engagement strategies to optimize organizational outcomes in an era of hybrid work arrangements.